2018
DOI: 10.3171/2018.6.peds18136
|View full text |Cite
|
Sign up to set email alerts
|

Examining the need for routine intensive care admission after surgical repair of nonsyndromic craniosynostosis: a preliminary analysis

Abstract: OBJECTIVEAt British Columbia Children’s Hospital (BCCH), pediatric patients with nonsyndromic craniosynostosis are admitted directly to a standard surgical ward after craniosynostosis surgery. This study’s purpose was to investigate the safety of direct ward admission and to examine the rate at which patients were transferred to the intensive care unit (ICU), the cause for the transfer, and any patient characteristics that indicate higher risk for ICU care. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…The single-center design confers an advantage relative to other published studies, as discussed above, but it may limit the generalizability of our data to other centers, where treatment and hospitalization protocols may differ significantly, especially with regard to postoperative ICU care. Bonfield et al 5 and Wolfswinkel et al 41 ICU admission after open CVR, and elimination of ICU care may represent a significant reduction in overall hospital charges. The financial data available for our study do not specify the subgroups of charges comprising the overall hospital fee, and as such we cannot identify a single component responsible for the large difference in hospital fees between open and endoscopic treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The single-center design confers an advantage relative to other published studies, as discussed above, but it may limit the generalizability of our data to other centers, where treatment and hospitalization protocols may differ significantly, especially with regard to postoperative ICU care. Bonfield et al 5 and Wolfswinkel et al 41 ICU admission after open CVR, and elimination of ICU care may represent a significant reduction in overall hospital charges. The financial data available for our study do not specify the subgroups of charges comprising the overall hospital fee, and as such we cannot identify a single component responsible for the large difference in hospital fees between open and endoscopic treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, other groups have also shown that intensive care admission after the surgical repair of nonsyndromic craniosynostosis is not routinely indicated. 9 In our patient's case, the hemoglobin level obtained 1 hour postoperatively was 8.9. She was transferred to the floor and discharged on postoperative day 1.…”
Section: Minimally Invasive Strip Craniectomy For Metopic Craniosynostosis Using a Lighted Retractormentioning
confidence: 49%
“…ICU admissions in 18 patients resulted from intraoperative issues and complications. These included vessel lacerations (5), significant blood loss (5), dural tears (4), difficult intubation or extubation (3), hypotension (3), intraoperative arrest or resuscitation (2), decreased perfusion (1), possible seizures (1), and extended time in the sphynx position (1). Several patients had constellations of related complications leading to ICU admission.…”
Section: Reasons For Icu Admissionmentioning
confidence: 99%
“…Several patients had constellations of related complications leading to ICU admission. An additional 12 ICU admissions resulted from PACU difficulties, including breathing difficulty or apnea (8), pain control issues (2), bradycardia or tachycardia (2), post-operative hemorrhage (1), facial edema (1), prolonged recovery from anesthesia (1), and possible seizures (1). Several patients had multiple PACU difficulties leading to ICU admission.…”
Section: Reasons For Icu Admissionmentioning
confidence: 99%
See 1 more Smart Citation